Comparison of venous couplers versus hand-sewn technique in 4577 cases of DIEP-flap breast reconstructions - A multicenter study - Heidekrüger, Paul; Fritschen, Uwe von; Möllhoff, Nicholas; Germann, Günter; Giunta, Riccardo; Zeman, Florian; Prantl, Lukas (Microsurgery, 2022)
Introduction Venous anastomosis remains to be a challenging step in microsurgical tissue transfer and venous complications constitute to a common reason for free flap failure. While several studies have compared mechanical vs. hand-sewn venous anastomoses, there is no large-series study comparing the type of anastomosis exclusively in DIEP flap breast reconstructions. Patients and Methods Between 2011 and 2019, 3926 female patients underwent 4577 free DIEP-flap breast reconstructions in 22 different breast cancer centers. Patient data was collected via an online database, files were screened and cases were divided into a hand- (HA) and a coupler-anastomosis (CA) group. Complications were accounted for and the two groups were then compared. Results Mean ischemia time was significantly shorter in the CA group (46.88 ± 26.17 vs. 55.48 ± 24.70 min; p < .001), whereas mean operative time was comparable (316 ± 134.01 vs. 320.77 ± 120.29 minutes; p = .294). We found no significant difference between both groups regarding the rate of partial (CA: 1.0% vs. HA: 1.3%) and total flap loss (CA: 2.2% vs. HA: 1.8%). However, revision rates were significantly higher in the CA group (CA: 10.5% vs. HA: 7.9%; p = .003), with higher numbers of arterial (2.3 vs. 0.9%; p < .001) and venous thromboses (3.4 vs. 1.8%; p = .001) accounting for this finding. Conclusions All taken into account, our findings do support the feasibility of venous coupler anastomoses in principle, however the inflationary use of coupler devices should be evaluated critically.
Gesehen am 24.04.2024